Особливості цивільно-правового регулювання інвестиційної діяльності в Україні - Федоров, Гліб Омелянович; Fedorov, Gleb (ВД "Гельветика", 2019)
Наукова стаття присвячена дослідженню цивільно-правового регулювання інвестиційній діяльності в Україні. У статті на основі комплексного науково-методологічного аналізу й дослідження різних підходів учених до вказаної проблематики виокремлено власний структурно-методологічний підхід у процесі формування інвестиційного іміджу відповідного територіального об’єкта, що враховував би особливості всіх цільових груп інвесторів. Ключовим аспектом пропонованого підходу є наявність можливості коригування іміджу, внесення змін в іміджеву програму. Зазначений підхід поділено на три ключові етапи: підготовчий етап, етап розроблення й етап реалізації.

The scientific article is devoted to the study of civil law regulation of investment activity in Ukraine. It was found out that the factors that make up investment attractiveness are the forces that provide the formation of preferences for the respective territory in the struggle for a limited range of investment resources. In science, there is a classical approach to the differentiation of factors of formation of investment attractiveness for institutional, economic and social, which exist at the micro, meso- and macro levels. Given the purpose of research, the image of the state should be determined by the macroeconomic factor of the formation of investment attractiveness. In Ukraine, investment activity takes place with the participation of the state. In our country, there is an investment law that has been adapted to EU norms and requirements. To date, there are more than fifty international agreements, the subject of which is the protection of investment activities and the promotion of such activities. But these benefits are mostly theoretical, since in practice, real support for investment projects by public authorities is mostly felt by managers of domestic enterprises whose interests are lobbied at higher levels of government. It is proved that the investment attractiveness of the region is a necessary and important prerequisite for the formation of a favorable investment climate. There are many approaches to assessing the investment attractiveness of the regions. Indicators of investment attractiveness are different. However, it should be noted that these developments in developed countries are quite common. Specialized research centers are currently working on solving such problem situations. In the article, taking into account the complex scientific and methodological analysis and research of different approaches of scientists in relation to the identified problem, the own structural and methodological approach in the process of forming the investment image of the corresponding territorial object is taken into account, taking into account the features of all target groups of investors. A key aspect of the proposed approach is the possibility of adjusting the image, making changes to the image program. This approach is divided into three key stages: the preparatory stage, the development phase and the implementation phase.
Федоров Г. О. Особливості цивільно-правового регулювання інвестиційної діяльності в Україні / Г. О. Федоров // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 18-23.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; інвестиційна діяльність; цивільно-правове регулювання; державне регулювання; державне управління; іноземні інвестиції; investment activity; civil law regulation; state regulation; public administration; foreign investments